PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS INVINITY CUBE MATERI PERPINDAHAN KALOR UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V DI SD NEGERI II PASINDANGAN - Siska Milawati; Nana Hendracipta; A. Syachruroji (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is based on the results of the needs analysis. The research comes from observations and interviews with teachers in one of the public schools, which is located in Cileles Lebak Banten. It is aimed to 1) find out how to develop Infinity Cube-based learning media on heat transfer materials to improve students’ learning activity at grade V, 2) find out the feasibility of learning media based on Infinity Cube heat transfer materials to improve students learning activities at grade V, and 3) find out students’ responses towards learning media based on Infinity Cube heat transfer material to increase students’ learning activity at grade V. The type of research used refers to the Research and Development method. Based on the research results from the validation of the material experts, the average score from the two experts was 87% in the very feasible category, the media expert test obtained an average score from the two media experts with a percentage of 80% in the very feasible category. The infinity cube media was tested on 24 fifth-grade students as a sample. Field trials of student responses from every aspect of material content, media display quality, and media significance obtained a score of 91.3% in the very feasible category. The students’ learning outcomes before using the media and after applying the second observation media from the acquisition of observational observations after the natural science learning subject process of heat transfer material using the Infinity Cube media obtained an increase based on the results of the first and second activity observation data analysis from 50% in enough category in the second observation to 90% in the high category, therefore, by using the media students seemed more active and motivated in learning. The recommendations for this research were 1) teachers in the use of media should pay more attention to making learning more fun so that learning did not seem monotonous, 2) with the media students were understood more what is explained and are more motivated in learning than before, 3) school needed to provide better facilities to support the learning process and students’ achievements, and 4) by conducting research in addition to developing learning media infinity cube, researchers, when were involved in schools, could develop further materials to follow-up in the use of learning media for teaching.